A NEW FIBRIN SEALANT FROM Crotalus durissus terrificus VENOM: APPLICATIONS IN MEDICINE - Barros, L. C. [UNESP]; Ferreira, R. S. [UNESP]; Barraviera, S. R. C. S. [UNESP]; Stolf, Hamilton Ometto [UNESP]; Thomazini-Santos, I. A. [UNESP]; Mendes Giannini, Maria José Soares [UNESP]; Toscano, E. [UNESP]; Barraviera, B. [UNESP] (Taylor & Francis Inc, 2009)
Fibrin sealant, a widely available tissue adhesive, has been used since 1940 in a variety of clinical applications. Commercially available fibrin sealant products are synthesized from bovine thrombin and human fibrinogen, which may transmit infectious diseases, and recipients may also develop antibodies against bovine thrombin. Bearing these disadvantages in mind, a new fibrin sealant was developed in 1989 by a group of researchers from the Center for the Study of Venoms and Venomous Animals, in São Paulo State, Brazil. The main purpose was to produce an adhesive fibrin without using human blood, to avoid transmitting infectious diseases. The components of this novel sealant were extracted from large animals and a serine proteinase extracted from Crotalus durissus terrificus snake venom. The applicability of this sealant was tested in animals and humans with beneficial results. The new fibrin sealant can be a useful tool clinically due to its flexibility and diversity of applications. This sealant is a biological and biodegradable product that ( 1) does not produce adverse reactions, ( 1) contains no human blood, ( 3) has a good adhesive capacity, ( 4) gives no transmission of infectious diseases, and ( 5) may be used as an adjuvant in conventional suture procedures. The effectiveness of this new fibrin sealant is reviewed and its development and employment are described.